2012
DOI: 10.21236/ada579552
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Air Force Hydroprocessed Renewable Jet (HRJ) Fuel Research

Abstract: Approved for public release; distribution unlimited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 3 publications
2
20
0
Order By: Relevance
“…As for the core-shell USY@Al-SBA-15, its medium/strong acidity was about 1.5 times that of the mesoporous Al-SBA-15 zeolite and less than that of USY. But the selectivity for C [4][5][6][7][8] hydrocarbons further decreased to 41.3 % and the selectivity for C [9][10][11][12][13][14][15] hydrocarbons significantly increased up to 35.7 %. These results indicate that the core-shell USY@Al-SBA-15 catalyst could significantly enhance the selective cracking for jet-range hydrocarbons by tailoring the acidity distribution in the mesopores.…”
Section: Influence Of the Support On The Hydroconversion Of Wcomentioning
confidence: 99%
See 1 more Smart Citation
“…As for the core-shell USY@Al-SBA-15, its medium/strong acidity was about 1.5 times that of the mesoporous Al-SBA-15 zeolite and less than that of USY. But the selectivity for C [4][5][6][7][8] hydrocarbons further decreased to 41.3 % and the selectivity for C [9][10][11][12][13][14][15] hydrocarbons significantly increased up to 35.7 %. These results indicate that the core-shell USY@Al-SBA-15 catalyst could significantly enhance the selective cracking for jet-range hydrocarbons by tailoring the acidity distribution in the mesopores.…”
Section: Influence Of the Support On The Hydroconversion Of Wcomentioning
confidence: 99%
“…These factors have led to the development of renewable and clean fuels produced from alternative sources [1][2][3][4]. Research on the conversion of biomass-based resources to biofuels is of current interest [4][5][6][7]. The main concern is the production of bio-jet fuel from renewable resources with a relatively low greenhouse gas life cycle and with sustainability at an affordable price [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrodeoxygenation step is followed by isomerization and cracking to get fuel of desired specifications like low temperature properties [83]. Hydroprocessing results in the formation of clean paraffinic fuels with high thermal stability, no aromatics and suphur and they are generally mentioned as hydroprocessed renewable jet fuels (HRJs) [84]. In the hydrodeoxygenation method, oxygen is most preferably removed as water and propane is one of the byproducts [85].…”
Section: Hydroprocessingmentioning
confidence: 99%
“…27,28,44). We now use the approach to extract quantitative VSP and virtual TSI values for the highly paraffinic hydrotreated renewable jet fuel (HRJ) POSF 7720 22 , which is based on camelina sativa biomass feedstock. Initial D1322 measurements indicated that the SP of this fuel exceeds the 50 mm limit of the standard SP apparatus.…”
Section: B Vsps Of Alternative Kerosenesmentioning
confidence: 99%